Characterisation and performance of a terfenol-d coated femtosecond laser inscribed optical fibre bragg sensor with a laser ablated microslot for the detection of static magnetic fields - Kalli, Kyriacos; Smith, Graham N.; Allsop, Thomas P.; Neal, Ron M.; Sugden, Kate; Culverhouse, Phil F.; Bennion, Ian; Koutsides, Charalambos (My University, 2011)
We present a novel device for the characterisation of static magnetic fields through monitoring wavelength shifts of femtosecond inscribed fibre Bragg grating and micromachined slot, coated with Terfenol-D. The device was sensitive to static magnetic fields and can be used as a vectoral sensor for the detection of magnetic fields as low as 0.046 mT with a resolution of ± 0.3mT in transmission and ± 0.7mT in reflection. The use of a femtosecond laser to both inscribe the FBGs and micromachine the slot in a single stage prior to coating the device significantly simplifies the fabrication.
Keywords: Plastic optical fibers; Bragg gratings; Microstructured polymer